Analytical and numerical investigation of the lift system stability of the air cushion vehicle fitted with closed inflated side seals. (March 2022) - Shabarov, Vasiliy; Peplin, Fedor; Kalyasov, Pavel; Shaposhnikov, Vitaliy
Abstract: An air cushion vehicle (ACV) with inflated side seals is a promising new type of air cushion supported vessels. These vehicles combine good amphibious abilities of conventional air cushion vehicles with seakeeping and maneuverability qualities pertinent to Surface Effect Ships (SES). One of the most important design concerns for the ACV with inflated side seals is eliminating vertical resonant oscillations of the vessel. These oscillations are caused by the unstable interaction between the air cushion and the inflated side seals. In this paper two mathematical models are derived to investigate the stability of an ACV with inflated side seals. The only difference between these models is that one of them takes into account the heave degree of freedom while the other one neglects it. It turns out that the simplified approach tends to underestimate the decrement of the oscillations compared to the full model. The analytical conditions of the lift system stability are derived from the simplified model. The developed models are applied to investigate the stability of the three ACVs with inflated side seals. The difficulties associated with scaling of the stability characteristics from the model tests are discussed. Highlights: The mathematical formulation allowing to determine stability characteristics of the lift system of the Air Cushion Vehicle fitted with Inflated Side Seals was developed. The analytical stability condition was derived from the simplified mathematical model. In particular case of rigid hulls the analytical criterion coincides with the known stability condition for SES. The developed models were applied to three imaginary vehicles. It was demonstrated that when the large vehicle is a scaled copy of the small one, then the large vehicle exhibites less stable behavior than the small one. Some feasible ways to increase the vehicle's stability were proposed.